HYPERREALITY AND NEO-GRAMSCIAN HEGEMONY IN CYBERNETICS - Neni Virginia Rachmatika; Budi Tri Santosa (Universitas Muhammadiyah Semarang, 2021)
This paper discusses advanced technology capable of detecting human behavior and psychology perfectly. Mica robots are a well-known artificial technology and are often shown on TV. But who would have thought, with his sophisticated system he was caught in a murder case, besides Mika Robot is also good at manipulating the human brain with his sexy tricks so that humans can obey his orders without being forced. Detectiv Rivera is confused by his strange attitude and he wonders whether a robot can be convicted of murder and whether he deserves a prosecutor as a protector in court. This study uses a qualitative descriptive research type with the aim of providing an overview and explaining the events that are happening without affecting or changing the variables in any way. The analysis technique is to understand the short story narrative and take ideas, then the ideas are reviewed through hegemony theory in order to achieve a desired result.